Hierarchical Order of User Preference Parameters in Adopting M-government Services - Mohammed Alneyadi, Rashed Hamad Rashed; Hamid, Nor Aziati Abdul (International Journal of Sustainable Construction Engineering and Technology, 2022)
United Arab Emirates (UAE) has taken continuous initiatives to ease in providing the government services. One of the initiatives is the M-government service but unfortunately, the rate of adopting the M-government service by the people is low. Thus, the government strives for improving the existing system and attracting the people towards the usage of M-government services. This study focused on identifying the common preferences of the people for adopting M-government services. Literature review found 30 people preference parameters and clustered into 6 groups which are Social Influence (SI), Perceived Compatibility (PC), Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Trust in Technology (TT) and Perceived Risk (PR). These preferences were used in the questionnaire development. The questionnaire was distributed randomly amongst the general public however only 263 completed questionnaire forms were received. The collected data from this survey was assessed for normality and multicollinearity and the finding indicated that the data was normal and had no major collinearity, hence the results obtained with the collected data can be generalized. The data was further analysed and found that the people of UAE have chosen the top publicâ€™s preference belong to the Social Influence category. While the highly agreed parameters are â€œpeople who are important to me would find using M-services beneficialâ€ and â€œgives social comfort to all usersâ€. From the findings of this study, it may benefit the government to take appropriate actions for the public interest towards the adoption of M-government services like devising strategies and mechanism to promote the M-government services in UAE.